2013
DOI: 10.1007/s00392-013-0559-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparing outcome of patients with coronary artery disease and dilated cardiomyopathy in ICD and CRT recipients: data from the German DEVICE—registry

Abstract: ICD and CRT patients in the DEVICE registry showed similar short-term outcome irrespective of their underlying disease etiology. Except older age and preponderance of males, clinical characteristics, device selection and outcome of ICD or CRT patients in the German DEVICE registry are comparable with patients from randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…In the present and in other studies, ICM compared with NICM patients tend to be older, predominantly male, have lower prevalence of left-bundle branch block (and hence, receive CRT-D less frequently) and last but not least, a higher mortality across reported clinical trials with ICD therapy. 12,16,17 However, separate analysis of the ICD therapy efficacy and outcomes in ICM and NICM patients was undertaken only in the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT) trial despite well known differences in pathophysiology, pathology, disease course, and outcomes. 2 Mortality reduction by ICD therapy related to underlying heart disease (ICM or NICM) was not uniform across reported clinical studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present and in other studies, ICM compared with NICM patients tend to be older, predominantly male, have lower prevalence of left-bundle branch block (and hence, receive CRT-D less frequently) and last but not least, a higher mortality across reported clinical trials with ICD therapy. 12,16,17 However, separate analysis of the ICD therapy efficacy and outcomes in ICM and NICM patients was undertaken only in the Sudden Cardiac Death in Heart Failure Trial (SCD-HeFT) trial despite well known differences in pathophysiology, pathology, disease course, and outcomes. 2 Mortality reduction by ICD therapy related to underlying heart disease (ICM or NICM) was not uniform across reported clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Among other studies with a similar objective, the Multicenter Automatic Defibrillator Implantation Trial‐Reduce Inappropriate Therapy (MADIT‐RIT) showed that high‐rate cut‐off or delayed VT therapy ICD programming resulted in reduction in inappropriate ICD therapy and mortality without an increase in syncopal events in patients with a primary preventive ICD indication . There is less definite evidence about ICD efficacy in NICM available from randomized trials although observational and registry data suggest similar occurrence of arrhythmias and ICD therapy benefit in both ICM and NICM patients . However, no studies so far have analyzed differential effects of novel ICD programming separately in patients with ICM and NICM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all the advances in pharmacological treatment, heart failure (HF) remains a leading cause of morbidity and mortality . For this reason, cardiac resynchronization therapy (CRT) is an important therapeutic option in the management of patients with symptomatic systolic HF . Biventricular pacing significantly improves cardiac output, quality of life, and functional capacity in patients with congestive HF.…”
Section: Introductionmentioning
confidence: 99%
“… 16 Patients are classified based on different categories in the CIED registries: first implantation versus generation replacement and primary prevention versus secondary prevention. 17 The TAVI registries usually need a dedicated heart team to determine participants’ criteria. 18 …”
Section: Resultsmentioning
confidence: 99%